2022
DOI: 10.1080/14017431.2022.2107234
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between six-minute walked distance and health-related quality of life in patients with chronic heart failure

Abstract: Objectives. To assess the relationship between the six-minute walk test (6MWT) and health-related quality of life (HRQL) in patients with chronic heart failure. Methods. Forty-six patients (37 men and 9 women) with chronic heart failure, mean age 68 (SD 9), NYHA II-III and EF 29 (9) % were included. They performed 6MWT and assessed HRQL using two tools, a Swedish version of the 36-item Short Form (SF-36) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). This was performed repeatedly during a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For example, one study highlighted the importance of stride length on 6MWT performance in HF patients, emphasising the need to consider biomechanical and technical variables during testing that may influence the distance walked and consequently its usefulness as a tool to assess functional capacity [ 57 ]. In addition, other research highlighted the relationship between the 6MWT and health-related quality of life in HF patients, suggesting that the 6MWT serves not only as a measure of functional capacity, but also as an indicator of patients’ perceptions of their health status and well-being [ 58 ]. Conversely, another study identified predictors of 6MWT performance in HF patients, improving our understanding of the determinants of functional capacity in this population [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study highlighted the importance of stride length on 6MWT performance in HF patients, emphasising the need to consider biomechanical and technical variables during testing that may influence the distance walked and consequently its usefulness as a tool to assess functional capacity [ 57 ]. In addition, other research highlighted the relationship between the 6MWT and health-related quality of life in HF patients, suggesting that the 6MWT serves not only as a measure of functional capacity, but also as an indicator of patients’ perceptions of their health status and well-being [ 58 ]. Conversely, another study identified predictors of 6MWT performance in HF patients, improving our understanding of the determinants of functional capacity in this population [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For DMD, higher utility values would be expected in patients with greater functional abilities and lower utilities in patients with lesser functional abilities. While data are not presently available for DMD, this relationship has been observed between ambulatory function tests (like the 6MWT) and multidimensional measures of utility in other therapeutic areas (including muscular dystrophy in adults, cystic fibrosis, heart failure or other pulmonary diseases for example) [ 24 27 ]. Whether a similar relationship exists between measures of motor performance (such as the NSAA) and utility has not previously been investigated in DMD.…”
Section: Introductionmentioning
confidence: 99%